Analysis of Public Views and Attitudes towards the Preservation of Tembang Cianjuran Traditional Art Culture - Casminih, Casminih; Hufad, Achmad; Sardin, Sardin (Journal of Ecohumanism, 2024)
Tembang Cianjuran is a traditional art originating from Cianjur Regency. This traditional art is one of the cultural treasures of West Java and Indonesia. This traditional art contains philosophical meaning, local wisdom, morals, and presents life values ​​that are useful for the community that owns it. However, currently Tembang Cianjuran is facing challenges in terms of its preservation. As times change, Tembang Cianjuran is increasingly marginalized due to the presence of contemporary art which is preferred by the younger generation. Apart from the effects of globalization, what is more important regarding the preservation of the Tembang Cianjuran traditional art is the views and attitudes of the community itself. This research aims to explore the views and attitudes of the people of Cianjur towards the existence and efforts to preserve Tembang Cianjuran. The research design used is a quantitative approach with survey methods. Data collection was carried out by distributing questionnaires to 172 respondents who were residents of Cianjur. The questionnaire was distributed via a goggle form which was forwarded via WhatsApp. The results of the research show that people consider Tembang Cianjuran as a symbol of community pride. In addition, they argue for the need for conservation measures. They also said that society must have responsibility for preserving traditional arts. It is hoped that the results of this research will provide insight into people's views and attitudes towards the importance of preserving traditional art. The implication of this research is that it can provide an overview of community support for preserving the traditional art of Tembang Cianjuran.